Synthesis of aminoacetamide substituted naphthalimide derivatives - Sharma, Sheryl (My University, 2015)
Monoallylated and Diallylated derivatives of nitro naphthalimide were synthesized in good yields. Monoallylated compound was selectively reduced and then acylated with chloroacetyl chloride followed by nucleophilic substitution with secondary amines viz., morpholine, pyrrolidine and piperdine to give moderate to excellent yields of products. These synthesized compounds were well characterized by 1H and 13C NMR spectrometry. These compounds will further been used for anticancer activity as well as DNA binding.
M.Sc.-Chemistry-Thesis
Keywords: Napthalimide; Allylation; Nucleophilic substitution; chemistry; scbc